Distal biceps tendon repair via new knotless endobutton fixation: A biomechanical study. (June 2021) - Rutka, Victor; Weppe, Florent; Duprey, Sonia; Gras, Laure-Lise
Background: Distal biceps tendon repair using endobutton fixation has shown the best biomechanical results in terms of pullout strength. Here, we compared Sethi's enhanced tension adjustable endobutton technique known as the "tension slide technique" to a new knotless endobutton fixation technique without a post-fixation screw. Our new approach is as effective as the tension slide technique in terms of pullout strength and gapping after early mobilization. Methods: A biomechanical cadaveric study with 16 paired arms was performed. With the radius held in place, the distal biceps tendon was loaded at 100 N for 500 cycles and the load was then increased until failure. Gapping after loading cycles and maximum load to failure were recorded and compared. Results: Median bone-tendon gapping was 5.77 mm (interquartile range (IQR) 4.84–9.11) for tension slide technique and 4.72 mm (IQR 1.77–6.16) for the knotless fixation (p = 0.047). Median load to failure was 257.87 N (IQR 222.07–325.35) in the tension slide technique group and 407.78 N (IQR 358.54–485.20) in the knotless group (p = 0.047). Discussion: The knotless endobutton provides better pullout strength and elongation results compared to the tension slide technique without the use of an interference screw, allowing early mobilization in order to faster return to daily living activities. Level of evidence: Basic science study.